Верхом на "Титанике": [роман] / Дарья Донцова - Донцова Дарья Аркадьевна (Иронический детектив, 2009)
Экземпляры: п/ф (20170306) / Инвентарный номер: 50836 / Цена: 50.00 / Сис.шифр: Р2 / Авт.знак: Д 67 / ГРНТИ: 17.82 / ББК: 84 (2 Рос=Рус)6-4